MATH TEXTBOOKS: POINT, LINE AND PLANE OF EUCLIDEAN GEOMETRY AND THE DIDACTIC TRANSPOSITION - Oliveira, Marcilio Martins de; Bastos, Samuel Edmundo Lopez (Cadernos de Educação Tecnologia e Sociedade, 2019)
This study presents a discussion on the area of plane geometry or non-Euclidean geometry, having as focus the primitive ones of plane geometry: point, line and plane. As the name itself refers to this geometry is from the work of the Greek mathematician Euclid of Alexandria, whose work dates back to approximately 300 BC. As theoretical contribution was the theory of Didactic Transposition the French Yves Chevallard (1991), this theory refers briefly to the changes and transformations that you know suffers from your appearance in the scientific community to your entry in the living room class. A research on textbooks of mathematics 6th grade belonging to several times. On choice of textbooks of mathematics, were taken as the basis year of 1985, the date on which the creation of the National Textbook Program (PNLD) and the year of 1996 date of implementation of the new guidelines and Bases of Brazilian Education (LDB 9394/96). The textbooks of mathematics were chosen because they are one of the means used for the input of knowledge in the classroom. In this research paper was used qualitative research and documentation, the books were analyzed one by one, in order to understand how was the process of addressing the concepts of point, line and plane in math textbooks and the scientific community. The paper presents a theoretical discussion involving the textbooks, the PNLD and the work of Euclid-Elements.